2020
DOI: 10.1002/emp2.12153
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided trigger point injection for piriformis syndrome in the emergency department

Abstract: Piriformis syndrome, a myofascial pain disorder characterized by deep gluteal pain that radiates to the ipsilateral lower back and/or posterior thigh, is an underreported cause of low back pain frequently misdiagnosed in the emergency department (ED). Often refractory to oral pain medications, this syndrome can be debilitating. Ultrasound‐guided trigger point injection of the piriformis muscle can treat piriformis syndrome, but no previous reports exist in the emergency medicine literature. This case series de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Through rectal palpation, Abbott ( 2009 ) determined painful nodules on the piriformis muscle at 4–5 and 7–8 oclock positions. Bevilacqua Alén et al ( 2016 ) and Aquino-Jose et al ( 2020 ) performed an ultrasound-guided intramuscular drug injection into the piriformis. Gupta et al ( 2017 ) injected dye through the vagina in fresh cadaver specimens and found that the obturator internus muscle was located at the 1 and 11 o’clock positions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through rectal palpation, Abbott ( 2009 ) determined painful nodules on the piriformis muscle at 4–5 and 7–8 oclock positions. Bevilacqua Alén et al ( 2016 ) and Aquino-Jose et al ( 2020 ) performed an ultrasound-guided intramuscular drug injection into the piriformis. Gupta et al ( 2017 ) injected dye through the vagina in fresh cadaver specimens and found that the obturator internus muscle was located at the 1 and 11 o’clock positions.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pelvic wall muscle spasm can be clinically diagnosed via electromyography or vaginal or rectal palpation to identify whether there are nodules in the pelvic wall muscles and relevant painful areas (Aquino-Jose et al 2020 ; Papadopoulos and Khan 2004 ). Treatment options include massage or intramuscular botulinum toxin A (BTX-A) injection to relax the muscles (Fishman et al 1998 ; Fowler et al 2014 ; Meknas et al 2003 ; Santamato et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on US-guided treatment of the piriformis syndrome have shown safety and good symptom relief (27,37,38) . According to Aquino-Jose et al, successful US-guided injection of a short-acting local anesthetic into the piriformis muscle leads to pain relief for up to 48 hours (38) . In a randomized controlled trial, no difference in outcome was observed between intramuscular deposition of a local anesthetic and corticosteroid versus local anesthetic only, which gives the idea that piriformis syndrome is mostly muscular in origin, and corticosteroids do not give an varies from 5 to 8%, although the actual rate is probably higher due to the overlap in the clinical presentation with other conditions (25) .…”
Section: Piriformis Syndromementioning
confidence: 99%
“…If schiatic nerve hydrodissection is attempted, the needle is progressed through the muscle until perineural position of the needle tip ( Fig. 3 ) ( 36 , 38 ) . In the publication by Chang et al ., a video presentation of the US-guided injection provides good visualization of the procedure ( 39 ) .…”
Section: Piriformis Syndromementioning
confidence: 99%
See 1 more Smart Citation